Structural breaks, inflation and interest rates: Evidence from the G7 countries - Jesús Clemente; María Dolores Gadea; Antonio Monta\~nés; Marcelo Reyes (Econometrics, 2017)
This study reconsiders the common unit root/co-integration approach to test for the Fisher effect for the economies of the G7 countries. We first show that nominal interest and inflation rates are better represented as I(0) variables. Later, we use the Bai-Perron procedure to show the existence of structural changes in the Fisher equation. After considering these breaks, we find very limited evidence of a total Fisher effect as the transmission coefficient of the expected inflation rates to nominal interest rates is very different than one.
Keywords: C22; E43; 330; unit roots; structural breaks; interest rates; inflation; Fisher effect